2020
DOI: 10.14336/ad.2020.0630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Progression and Prolonged Viral Shedding in COVID-19 Patients: A Multicenter Study

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic associated with a high mortality. Our study aimed to determine the clinical risk factors associated with disease progression and prolonged viral shedding in patients with COVID-19. Consecutive 564 hospitalized patients with confirmed COVID-19 between January 17, 2020 and February 28, 2020 were included in this multicenter, retrospective study. The effects of clinical factors on disease progression and prolonged viral shedding were analyzed using logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…In the WHO-issued interim guidelines on “Clinical management of severe acute respiratory infection when COVID-19 is suspected” (published on March 13, 2020) [ 179 ], corticosteroids are not recommended unless otherwise indicated [ 180 ]. Nevertheless, some scholars think that the application of pulsed dose or long-term high dose, or early administration of corticosteroids to treat serious viral pneumonia can affect virus clearance rate [ 178 , 181 ] or survival [ 182 ]. On the contrary, some researchers found that adjuvant therapy with low-dose corticosteroids could reduce mortality in critical cases [ 183 ].…”
Section: Current Therapeutics and Drug Developmentmentioning
confidence: 99%
“…In the WHO-issued interim guidelines on “Clinical management of severe acute respiratory infection when COVID-19 is suspected” (published on March 13, 2020) [ 179 ], corticosteroids are not recommended unless otherwise indicated [ 180 ]. Nevertheless, some scholars think that the application of pulsed dose or long-term high dose, or early administration of corticosteroids to treat serious viral pneumonia can affect virus clearance rate [ 178 , 181 ] or survival [ 182 ]. On the contrary, some researchers found that adjuvant therapy with low-dose corticosteroids could reduce mortality in critical cases [ 183 ].…”
Section: Current Therapeutics and Drug Developmentmentioning
confidence: 99%
“…In our study, we observed major differences in the distributions of pre-existing medical conditions, gender, and age across different COVID-19 outcomes, improving our understanding of the risk factors related to COVID-19. Among various pre-existing medical conditions in COVID-19 patients, the most frequently reported diseases were cardiovascular diseases, diabetes, and chronic respiratory diseases [1][2][3][4]. The virus that causes COVID-19 is known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [5].…”
Section: Figure 1 Distributions Of Pre-existing Medical Condition Gmentioning
confidence: 99%
“…The fatality rate also increases with patients’ age [ 2 ]. A recent article published in Aging & Disease has reported that older age and pre-existing medical conditions of hypertension and chronic obstructive pulmonary diseases were independent risk factors for the progression to severe or critical pneumonia in 564 hospitalized COVID-19 patients [ 3 ], which have raised serious concerns. However, there is scarcity of data on the distributions of the pre-existing medical conditions, gender, and age across different COVID-19 outcomes in a large cohort.…”
mentioning
confidence: 99%
“…In uence analyses identi ed four studies 15,23,26,32 , with an excessive in uence on the overall results, of which two studies with extreme sample size are the excluded studies of predesign in the sensitivity analyses (Supplementary Figure 8). All the sensitivity analyses based on adjusted HRs showed a similar result with that from the main analysis (Supplementary Figure 1-7).…”
Section: Risk Of Viral Clearance Delaymentioning
confidence: 99%